Studi Batuan Asal (Provenance) dan Diagenesis Batupasir Formasi Ngrayong Daerah Tempuran dan Sekitarnya, Kecamatan Medang, Kabupaten Blora, Jawa Tengah - Faizal Abdillah (Geological Engineering E-Journal, 2013)
Geographically, the study area is at 9241000 mN - mE 9235000 mN and 548 000 - 555 000 mE (UTM WGS 84, Zone 49S) and administratively located in Tempuran Regional, District Medang, Blora regency, West Java Province. Based on physiographic zones Van Bemmelen (1949) study area into zones Antiklinorium Rembang - Madura.The research was conducted to determine rock origins (provenance) and the process that occurs in sandstone diagenesis Ngrayong formation, and to investigate the depositional environment Ngrayong formations that exist in the study area.The form of field data that collected in is stratigraphic cross-section measurements, the identification of the physical properties of rock and rock samples from observation stations scattered in research sites. Petrographic analyzes performed on thin section based on the rock samples.Based on the analysis of the mineral composition of sandstones quartz, feldspar and lithic fragments at Dickinson and Suzcek QFL diagram, 1979, Sandstones study area is estimated to come from recycled orogen of height karimunjawa formed by the collisions. While symptoms of diagenesis recorded from petrographic analysis showed sandstones having eogenesis stages in the meteoric environment based on red beds forming. Sandstone also experienced mesogenesis stages with symptoms such as compaction diagenesis with sutures contact, dissolving feldspar,, quartz overgrowth and cementation. Stages telogenesis indicated by deformation of outcrop in the study area. Ngrayong Formation depositional environment on the area of research is in deltaic to a shallow sea with river-dominated type.